Observation of two resonances in the Λ_{b}^{0}π^{±} systems and precise measurement of Σ_{b}^{±} and Σ_{b}^{*±} properties - Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Aidala, CA; Ajaltouni, Z; Akar, S; Albicocco, P; Albrecht, J; Alessio, F; Alexander, M; Albero, A; et al. (American Physical Society, 2019)
The first observation of two structures consistent with resonances in the final states Λ_{b}^{0}π^{-} and Λ_{b}^{0}π^{+} is reported using samples of pp collision data collected by the LHCb experiment at sqrt[s]=7 and 8 TeV, corresponding to an integrated luminosity of 3  fb^{-1}. The ground states Σ_{b}^{±} and Σ_{b}^{*±} are also confirmed and their masses and widths are precisely measured.